PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING (PBL) TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI IPA SMA NEGERI 1 BATIPUH KABUPATEN TANAH DATAR - Rinta Doski Yance (Universitas Negeri Padang, 2013)
Abstract — This research is purposed to investigate the effect of using project based learning (PBL) toward learning physic of exact eleven grade senior high school students in SMAN 1 Batipuh. Research method that is used is quasi experiment with randomized control research group only design research. The populations of this research are students of exact eleven grade study year 2012/2013. Taking sample done by using purposive sampling technique and the classes chosen are for experiment class and for experiment class. Research data collecting techniques are written test for cognitive aspect, observation sheet for affective aspect, score rubric for psychomotor aspect and score rubric result project for experiment class. Research data analysis technique using t test in real degree 0,05. Result of research in cognitive aspect is gotten 80,2 for experiment class and 75,3 for control class. Result of research analysis t test is gotten =2,08 and =2,02. In affective aspect is obtained 13,4 for experiment and 11,61 for control class. Result of analysis t test is gotten =2,86 and =2,02 in real degree 0,05, acceptance criteria Hi if ,< < , means that Hi is acceptable.Psychomotor aspect is obtained 77,83 for experiment class higher control class and 74,91 for control class. Result of analysis t test is gotten =2,92 and =2,02 in real degree 0,05, acceptance criteria Hi if ,< < , means that Hi is acceptable. Keywords — PBL, Hasil Belajar Fisika, SMA N 1 Batipuh